2020
DOI: 10.1001/jamanetworkopen.2020.13249
|View full text |Cite
|
Sign up to set email alerts
|

Effect of D-Cycloserine on the Effect of Concentrated Exposure and Response Prevention in Difficult-to-Treat Obsessive-Compulsive Disorder

Abstract: IMPORTANCE Evidence is lacking for viable treatment options for patients with difficult-to-treat obsessive-compulsive disorder (OCD). It has been suggested that D-cycloserine (DCS) could potentiate the effect of exposure and response prevention (ERP) treatment, but the hypothesis has not been tested among patients with difficult-to-treat OCD. OBJECTIVE To evaluate whether DCS potentiates the effect of concentrated ERP among patients with difficult-to-treat OCD. DESIGN, SETTING, AND PARTICIPANTS The study was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 44 publications
4
18
0
Order By: Relevance
“…A meta-analysis of these three studies found small, nonsignificant positive effects of riluzole on obsessive-compulsive symptoms 39 . Other substances such as glycine, an NMDAR co-agonist, and D-cycloserine, a partial co-agonist at the glycine site of the NDMAR, have also been tested for treating OCD, with the latter producing negative results 40–42 and glycine showing a trend toward therapeutic effects 43 . Bitopertin is a glycine reuptake inhibitor studied mainly for negative symptoms of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of these three studies found small, nonsignificant positive effects of riluzole on obsessive-compulsive symptoms 39 . Other substances such as glycine, an NMDAR co-agonist, and D-cycloserine, a partial co-agonist at the glycine site of the NDMAR, have also been tested for treating OCD, with the latter producing negative results 40–42 and glycine showing a trend toward therapeutic effects 43 . Bitopertin is a glycine reuptake inhibitor studied mainly for negative symptoms of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the sample size limited the number of variables that could be included in the regression analyses. It is also a limitation that the study did not include patients that had been previously treated with EX/RP, because there was an ongoing parallel study for difficult-to-treat OCD-patients ( 51 ). Therefore, future studies should investigate the role of adherence using larger samples and in patients that have relapsed or not responded to previous treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In a preliminary randomised controlled trial (RCT), Farrell et al (2013) reported significantly greater improvements in OCD symptoms for difficult-to-treat children and adolescents with OCD (n = 17) who received DCS augmented ERP relative to placebo (PBO) from posttreatment to 1-month follow-up. In contrast however, a large RCT (n = 163) of difficult-to-treat adults with OCD (Kvale et al, 2020) did not demonstrate overall benefits for DCS augmented intensive ERP (two doses over 2 consecutive days), despite earlier pilot RCTs with adults reporting significant benefits for DCS after only a few sessions of ERP (Kushner et al, 2007;Wilhelm et al, 2008). In a large RCT of youth, Storch et al (2016) (n = 142) found no overall benefit for weight-adjusted DCS augmented CBT relative to placebo on OCD severity following 10 sessions of CBT, 7 of which were augmented with DCS/PBO.…”
Section: Introductionmentioning
confidence: 98%